Shear Failure of RC Dapped-End Beams - Aswin, M. (Hindawi Publishing Corporation, 2015)
Reinforced concrete dapped-end beams (RC-DEBs) are mainly used for precast element construction. RC-DEBs generally are recessed at their end parts and supported by columns, cantilevers, inverted T-beams, or corbels. The geometric discontinuity of dapped-end beams evokes a severe stress concentration at reentrant corners that may lead to shear failure. Therefore, stress analysis is required at the reentrant vicinity for design requirement of these beams. Four large-scale RC-DEBs specimens were prepared, cast, and tested up to failure. Three parameters were investigated: amount of nib reinforcements, main flexural reinforcements, and concrete type at the dapped-end area. Finite element analysis using Vec2 was also conducted to predict the behavior of RC-DEBs. It has been found that highest stresses concentration factors occur at the reentrant corners and its vicinity. By using engineered cementitious composite (ECC) in the dapped-end area, the failure load has increased by 51.9, while the increment in the failure load was 62.2 and 46.7 as the amount of nib reinforcement and main flexural reinforcement increased, respectively. In addition, Vec2 analysis has been found to provide better accuracy for predicting the failure load of RC-DEBs compared to other analysis approaches. Â© 2015 Muhammad Aswin et al.